Effect of SiO2 amount on heterogeneous base catalysis of SiO2@Mg–Al layered double hydroxide. Issue 49 (6th August 2018) - Shirotori, Mahiro; Nishimura, Shun; Ebitani, Kohki
Abstract : The effects of SiO2 amount on the base catalysis of highly active finely crystallized Mg–Al LDH(s) prepared by the co-precipitation method with coexistence of SiO2 sphere seeds were investigated by XRD, ICP, 29 Si NMR, TEM-EDS and other techniques. Abstract : The effects of SiO2 amount on the base catalysis of highly active finely crystallized Mg–Al type layered double hydroxides prepared by the co-precipitation method with coexistence of SiO2 spheres, denoted as SiO2 @LDHs, were investigated. With the Si/(Mg + Al) atomic ratios of 0–0.50, the highest activity for the Knoevenagel condensation was observed in the case of Si/(Mg + Al) = 0.17, as the reaction rate of 171.1 mmol g(cat) −1 h −1 . The base activity increased concomitantly with decreasing LDH crystallite size up to Si/(Mg + Al) atomic ratio of 0.17. However, above the Si/(Mg + Al) atomic ratio of 0.17, the reaction rate and TOFbase were decreased although the total base amount was increased. Results of TEM-EDS and 29 Si CP-MAS NMR suggest that the co-existing SiO2 causes advantages for dispersion and reduction of the LDH crystallite to improve the base catalysis of SiO2 @Mg–Al LDH, whereas the excess SiO2 species unfortunately poisons the highly active sites on the finely crystallized LDH crystals above a Si/(Mg + Al) atomic ratio of 0.17. According to these results, we inferred that the amount of spherical SiO2 seeds in the co-precipitation method is an important factor to increase the base catalysis of SiO2 @LDHs; i.e. the control of Si/(Mg + Al) atomic ratio is necessary to avoid the poisoning of highly active base sites on the LDH crystal.